Crossover Cases of High‐Conflict Families Involving Child Protection Services: Ontario Research Findings and Suggestions for Good Practices. (July 2017) - Houston, Claire; Bala, Nicholas; Saini, Michael
Abstract : Child protection services (CPS) are increasingly becoming involved in high‐conflict separations and the related custody and access proceedings. CPS involvement is often necessary to respond to abuse or neglect allegations or protect children from emotional harm. However, these crossover cases are very challenging for family justice professionals. This article reports on research on crossover cases in Ontario, including an analysis of reported court decisions, a survey of CPS staff, and interviews with family justice professionals. We suggest clearer CPS policies; improved understanding of respective professional roles; CPS summary reports for family courts; increased interagency coordination, communication, and training; and use of judicial case management. Key Points for the Family Court Community: It is increasingly common for high‐conflict separations to result in reports to child protection services (CPS) and for concurrent custody and access and child protection proceedings to occur. CPS reports often allege domestic violence, emotional abuse, and sexual abuse; a relatively high number of CPS reports made in the context of high‐conflict separations are unsubstantiated. There is limited research on the effect of CPS intervention in high‐conflict separations or best practices. In some locales, CPS may be the only source of publicly funded social services for high‐conflict families. We suggest good practices for CPS and family justice professionals dealing with high‐conflict separations.